Facilitation of Gastrointestinal (GI) Tract Microbiome-Derived Lipopolysaccharide (LPS) Entry Into Human Neurons by Amyloid Beta-42 (Aβ42) Peptide - Walter J. Lukiw; Walter J. Lukiw; Walter J. Lukiw; Wenhong Li; Wenhong Li; Taylor Bond; Yuhai Zhao; Yuhai Zhao (Frontiers in Cellular Neuroscience, 2019)
Human gastrointestinal (GI)-tract microbiome-derived lipopolysaccharide (LPS): (i) has been recently shown to target, accumulate within, and eventually encapsulate neuronal nuclei of the human central nervous system (CNS) in Alzheimer’s disease (AD) brain; and (ii) this action appears to impede and restrict the outward flow of genetic information from neuronal nuclei. It has previously been shown that in LPS-encased neuronal nuclei in AD brain there is a specific disruption in the output and expression of two AD-relevant, neuron-specific markers encoding the cytoskeletal neurofilament light (NF-L) chain protein and the synaptic phosphoprotein synapsin-1 (SYN1) involved in the regulation of neurotransmitter release. The biophysical mechanisms involved in the facilitation of the targeting of LPS to neuronal cells and nuclei and eventual nuclear envelopment and functional disruption are not entirely clear. In this “Perspectives article” we discuss current advances, and consider future directions in this research area, and provide novel evidence in human neuronal-glial (HNG) cells in primary culture that the co-incubation of LPS with amyloid-beta 42 (Aβ42) peptide facilitates the association of LPS with neuronal cells. These findings: (i) support a novel pathogenic role for Aβ42 peptides in neurons via the formation of pores across the nuclear membrane and/or a significant biophysical disruption of the neuronal nuclear envelope; and (ii) advance the concept that the Aβ42 peptide-facilitated entry of LPS into brain neurons, accession of neuronal nuclei, and down-regulation of neuron-specific components such as NF-L and SYN1 may contribute significantly to neuropathological deficits as are characteristically observed in AD-affected brain.